Microalbuminuria in Chronic Hepatitis B Infection - Kilic, Mehmet; Taskin, Erdal; Sen, Yasar; Dogan, Yasar (Indian Acad Pediatrics, 2010)
We examined for microalbuminuria in patients with hepatitis B virus (HBV) infection, and the effect of antiviral treatment. Group I consisted of 38 patients who were inactive HbsAg carriers; group II included 21 HBeAg positive patients with chronic HBV infection who responded to antiviral treatment at 6 months; group III consisted of 24 patients with chronic HBV infection who did not respond to treatment at the end of 6 months; and group IV consisted of healthy controls. Initial level of microalbuminuria was significantly higher in group II compared to the levels measured at 3, 6, and 9 months (P<0.001). Although, there was a significant difference in microalbuminuria at initial and 3 months between group I and group II (P<0.001), no differences were found at 6 and 9 months. There was no significant difference betweeen group II and group III in terms of urine microalbuminuria at the beginning of the study, but statistically significant differences were determined at 3, 6, and 9 months (P<0.001). The measurement of microalbuminuria may indicate a preclinical renal damage, associated with chronic HBV infection. It may also be used to determine the response to treatment with interferon and lamivudine in children with HBV infection.
Keywords: Children; Hepatitis B; Microalbuminuria; Renal damage; Treatment